From Anime to Digital Games: Japanese Cultural Diplomacy in the Perspective of International Relations - Faisal, Ahmad; Putri, Sylvia Octa; Setiana, Soni Mulyawan; Arifin, Muhammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Popular culture has become an increasingly visible part of state diplomacy, although its role in International Relations is still not examined as systematically as military or economic power. This article discusses how Japan employs anime and digital games as instruments of cultural diplomacy and soft power. Using a qualitative approach, the analysis draws on policy documents, media reports, and selected cases interpreted through soft power theory and constructivism. The discussion shows that the international circulation of Japanese popular culture initially developed through fan communities and commercial networks before being incorporated into state-led programs such as the Cool Japan Initiative. Anime and games contribute to nation branding, support the reconstruction of Japan’s post-war identity, and generate substantial economic value. Their influence, however, is not unlimited. Historical tensions with China and Korea, competition from other Asian cultural industries, and dependence on global digital platforms continue to shape their diplomatic reach. Digital games are especially important because players do not merely watch a representation of Japan; they interact with narratives, characters, and values over time. The article therefore argues that cultural industries should be understood as both economic assets and practical instruments of contemporary diplomacy.